TRANSLATION ENGLISH-INDONESIA: LEARNING DEVELOPMENT BASED HYBRID LEARNING IN POST-PANDEMIC ERA FOR EFL STUDENTS - Lena Marliana Harahap; Sholihatul Hamidah Daulay (UIN Sumatera Utara, 2022)
This study aims to describe the development of a Hybrid learning model in Translation: English-Indonesian learning for UINSU English Tadris students. researchers use the Borg and Gall model through ten steps. 30 research subjects were taken from the UINSU English Tadris study program population. Data were collected by observation techniques, questionnaires, and tests. Data analysis techniques use percentages, mean, and t-tests. The results of the validation research from experts I and II on the design of the hybrid learning model were an average of 4.34 in the very good category. Field test results I; average paratest 6.17 and posttest 6.60. Field test II average parates 6.63 and posttest 7.65. Field test III average paratest 6.72 and posttest 7. 69. Different test results through t-test on learning motivation t-count 9.254, student creativity 9.796, and learning outcomes 9.840 and it turns out that t-count> t-table 2.136 is proven there is a significant difference before using the model and after using the hybrid learning model. The conclusion of the study is that the hybrid learning model developed in this study is effectively used in Translation: English-Indonesian learning for UINSU English Tadris Program students.